A Framework Determining Service Level in a B2B Environment based on ITIL Framework - Hasanzadeh Hasanzadeh; mahsa Nazemi; Elahi Elahi; Zanjani Zanjani (Journal of Information Technology Management)
Rapid growth of e-commerce has made the competition quite different. In this new environment customers have wide choices and are looking forward to the support which guarantees the delivery of what they have chosen. This leads to complexity in the relationship between the provider and the customer which obviously is made more in a B2B environment. Service Level Agreement (SLA) is a key tool to manage this complexity. One of the current challenges in setting of SLAs is the gap between customer requirements and perceived characteristics of service by the provider. Unlike previous researches which only consider providers capability to provide service, this research looks at the other side of contract, customers, and presents a comprehensive framework of customer properties. Firstly, dimensions and indicators of the customer properties were identified through literature review and then, they were evaluated through experts’ survey. The detected dimensions in this framework were management, organization, human, knowledge, information, applications and infrastructure.